On the Issue of Dating the Cathedral Church of Surb Astvatsatsin in Avan - Ghazaryan, Avetik (History and Culture, 2026)
This study, aimed at dating the Cathedral Church of Surb Astvatsatsin in Avan, is based on a new comparative analysis, re-evaluation and re-substantiation of studies and historical facts on this topic using historical-ecclesiastical comparative, critical, analytical and descriptive methodology. As a result, a scientific analysis is put forward in the context of dating the Church of Surb Astvatsatsin. The results of the study of the problem under discussion are important for conducting multifaceted and interdisciplinary research. Medieval literary sources provide valuable information about the complex of the church of Surb Astvatsatsin, that is, the Cathedral Church and the residence of the Catholicos, but do not specify the date of construction. The main issues around which scientific discussions were conducted were the history of the monument, its dating, architectural composition, as well as lapidary inscriptions, which are important for the study of various historical and cultural issues not only in Armenia, but also in the region. Historical facts and medieval literary information are of great importance for the scientific study of the dating of the Surb Astvatsatsin Church, the comparative results of which provide an opportunity for a new scientific discussion on the issue of the discussed object. Thus, a comparative analysis of literary and historical data allows the Cathedral Church of Surb Astvatsatsin in Avan to be dated to the end of the 6th century, taking 591 as the beginning of construction and 597 as the completion. Accordingly, the data we provide also complement the point of view proposed by T. Toramanyan and allow for its re-substantiation.
Keywords: monuments; residence of the Catholicos; Armenian Chalcedonian Anti-See Catholicosate; church complex; Cathedral Church of Surb Astvatsatsin; Hovhan Bagarantsi